Is sclerosant injection mandatory after an epinephrine injection for arrest of peptic ulcer haemorrhage? A prospective, randomised, comparative study. Issue 9 (September 1993) - Lin, H J; Perng, C L; Lee, S D
Abstract : A prospective, randomised, comparative study was performed to assess the need for a pure alcohol injection after an epinephrine injection in the arrest of active peptic ulcer bleeding. Sixty four patients with active ulcer bleeding were enrolled in the study. The two groups (epinephrine and epinephrine plus pure alcohol) were matched for sex, age, site of bleed, endoscopic findings, shock, haemoglobin, and concomitant illness at randomisation. The volume of injected epinephrine in the epinephrine and the epinephrine plus pure alcohol groups mean (SD) was 6.0 (3.0) ml and 5.5 (3.0) ml respectively (p > 0.05). The volume of injected pure alcohol in the epinephrine plus pure alcohol group was 1.9 (1.1) ml. Bleeding was initially controlled in 31 (97%) of the epinephrine group and all of the epinephrine plus pure alcohol group. Rebleeding occurred in 11 (36%) of the epinephrine group and in five (16%) of the epinephrine plus pure alcohol group (p > 0.05). Rebleeding was successfully controlled in some patients with treatment by a second injection. Other patients had heat probe thermocoagulation or surgery. Ultimate haemostatic rates were 69% (22/32) and 88% (28/32) for the epinephrine and the epinephrine plus pure alcohol groups respectively (p > 0.05). The epinephrine plus pure alcohol group achieved a better haemostatic effect for spurting haemorrhage (9/10 v 5/11, p < 0.05). The need for emergency operations and blood transfusions were comparable in both groups. The stay in hospital were less in the epinephrine plus pure alcohol group (mean 4.3 v 7.1, p < 0.05). It is concluded that pure alcohol injection after an epinephrine injection can improve the haemostatic rate in patients with spurting haemorrhage and shorten the hospital stay for patients with active bleeding.